Accounting Graduates' Knowledge, Skills, and Attitude in the Industrial Age 5.0 - Syamsu Rijal (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This study aims to determine the knowledge, skills, attitude (KSA) that accounting graduates must possess in the industrial era 5.0 so that they remain relevant along with technological developments based on the perspectives of regulators, academics and graduate users. This type of research is qualitative research. In this study the researchers conducted interviews with informants. The informants in this study were the Chairperson of the Indonesian Institute of Accountants (IAI) in the West Java region, the Chairperson of the Managerial Accounting Study Program at Pasundan University and the HRD of companies in Bandung. The results of the research are based on the perspective of a student regulator, they must have internship experience, actively participate in seminars, problem solving skills and a good attitude. The academic perspective emphasizes academic value, being able to adapt, think critically, have leadership and have fighting power. The perspective of graduate users is that they have digital analysis skills, computer skills and are creative. In addition, the three perspectives also share the same view that accounting graduates must be technologically literate, have basic accounting knowledge, analytical skills, communication skills, have work experience, foreign language skills, professional certification, initiative, teamwork, integrity, thoroughness and detail, discipline. , responsibility and mutual respect.